Health Impact Assessments for Environmental Restoration: The Case of Caño Martín Peña - Perry Sheffield (Ubiquity Press, 2014)
Background: Health Impact Assessment (HIA) is a methodology for predicting the effects of a proposed policy or plan on health. A proposed environmental restoration and development plan presented an opportunity for an HIA in an environmental justice community surrounding the Martín Peña channel in San Juan, Puerto Rico. The HIA focused on the dredging of the channel, debris removal, road, sewer, and storm water infrastructure improvements, housing demolition, and resident relocation. Objective: The aim of this study was to determine the potential effects of the proposed plan on the community's health to inform the funding decision by the Puerto Rican legislature. As the first HIA in Puerto Rico, a secondary objective was to build HIA capacity in Puerto Rico. Methods: This HIA used community training, literature reviews, existing local studies, focus groups, interviews, and disease surveillance data to assess baseline health, determine expected effects, and build capacity. Findings: The Martín Peña community is experiencing deteriorating environmental conditions. Flooding and negative environmental exposures, such as mold, limits to physical activity, stress, chemical toxicants, pathogenic bacteria, and pests, are worsening. The higher rates of diseases, such as asthma and diarrhea, in the community compared with elsewhere in Puerto Rico appear to be largely attributable to these factors. Overall, the proposed plan is expected to improve many of these health disparities but the successful implementation depends on continued community acceptance and participation, particularly with the relocation process. Recommendations are for full financing and several mitigation efforts to avoid negative and preserve beneficial health consequences. Conclusions: As the first HIA in Puerto Rico, this assessment provided specific recommendations to benefit the health of the community affected by an environmental restoration and development plan and also capacity building for a larger audience in Puerto Rico. This approach could be generalized to other Latino environmental justice communities in Puerto Rico and abroad.